(untitled) - Lê, Minh Hiếu (Cần Thơ, 2020)
This article intended to discuss prominent issues in teaching Intercultural Communication (ICC) to English as a foreign language (EFL) - students through the pilot English Textbook-English 10 in Vietnamese high school level, especially at some high schools in the Mekong Delta. The concepts of culture, language and culture, teaching and evaluation ICC, and using application in teaching and learning ICC were defined respectively. Next, the characteristics and components of culture were presented as well. The relationship between language and culture would also be pointed out. Moreover, factors such as teaching, curriculum, and textbooks that had an impact on the success and failure of teaching culture to EFL high school students were examined. Besides, various uses on application in ICC teaching and learning would be explored. The result of data analysis from instruments: questionnaires and interviews would be presented and addressed. Additionally, the evaluation of cultural perception and ways to use applications for combination into the lessons would too be described. Furthermore, the advantages and disadvantages of using applications for teaching ICC in the high school language classroom would be mentioned after data analysis. Finally, some discussions and conclusions would be made.
Keywords: Tiếng Anh,English language; Dạy và học (Trung học),Study and teaching (Secondary)